Development of Ethno-STEM Integrated Teaching Materials on the Topic of Light Waves to Improve the Science Literacy of Grade XI Students - Sephiani, Nabila Paramita; Rusilowati, Ani (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to describe the characteristics, analyze validity, analyze practicality, and analyze the effectiveness of ethno-STEM integrated teaching materials of light wave materials to improve students' science literacy. This study uses the Research and Development (R&D) method with the ADDIE model, namely five stages: analysis, design, development, implementation, and evaluation. The population of this study is class XI students at SMAN 1 Cepiring with the research subjects of 68 students selected using purposive sampling techniques. The data collection technique used in this study used a test method in the form of a science literacy description test and a non-test method in the form of questionnaires and interviews. The data analysis techniques used in this study are in the form of the validity test of teaching materials, the practicality test of teaching materials, and the N-Gain test to analyze the effectiveness of teaching materials. The results of the study show that the teaching materials developed have characteristics that are presented in the features of "Let's Get to Know Culture", "Let's Observe", "Let's Think", "Let's Try", "Let's Solve", and "Let's Be Technological". Furthermore, the teaching material obtained validity with a score of 87.5% which was in the very valid category. Furthermore, based on the practicality test, a score of 96% was obtained where the teaching material was considered very practical to use, and was able to improve the science literacy of students in the medium category with an N-Gain score of 0.4571. Therefore, it can be concluded that the teaching materials are valid, practical, and can be used as a learning resource to improve students' science literacy.